Constitutional Guarantee for Indonesian Citizens as Practitioners of a Belief System: Jaminan Konstitusional bagi Warga Negara Penganut Aliran Kepercayaan di Indonesia - Muhammad Hoiru Nail (Indonesian Journal of Law and Islamic Law (IJLIL), 2023)
Article 29, Paragraph (2) of the 1945 Constitution of the Republic of Indonesia guarantees freedom for every citizen to embrace a religion and/or belief system. This constitutional basis ensures that adherents of religions and beliefs are granted an equal position. However, legal issues arose when Law of the Republic of Indonesia Number 24 of 2013, concerning Amendments to Law Number 23 of 2006 regarding Population Administration, discriminated against residents who adhered to beliefs by leaving the religion column blank for Family Cards and Electronic KTPs (Article 61, Paragraphs (1) and (2), and Article 64, Paragraphs (1) and (5) of the Population Administration Law). This research utilizes normative legal research methodology. The legal product was ultimately reviewed by the Constitutional Court, which acknowledged the presence of adherents of religious beliefs in the column of Electronic ID Card.